Green technology design approach for liveable park of Tasik Biru Kundang, Malaysia / Rijal Saffuan, Junaidah Ariffin and Zamreen Amin - Saffuan, Rijal; Ariffin, Junaidah; Amin, Zamreen (Universiti Teknologi MARA Cawangan Selangor, 2018)
Green Technology design approach is a new solution that must be applicable to preserve a nature and reduce the pollution. There are so much innovation could be used to in the development of the park to reduce the electricity use, eco-friendly and livable for the community. This paper aims to exemplify an effort by a group of students, through multi-professional inputs, in designing for a city facility that can add more towards a livable city. The results of the approach are multidisciplinary design that includes the idea from multiprofessional in making a livable park for community surroundings Tasik Biru Kundang, Kuang, Selangor, Malaysia.